Integration of learning management system with social networking sites / Sami F. A. Abuyousef - Sami F. A. , Abuyousef (2018)
The purpose of this study is to attain the integration of the LMS with SNS in order to enhance the e-learning process high level of engagement, collaboration and easing the sharing of the educational material by using the advantages and features of SNS, not delivering the content only. Today, SNS has become a phenomenon and it have been accepted by the age group of the students, such as any websites which influencing many aspects of students life that cause a changing in the student behavior and the educational process including the e-learning systems. In this study understanding the attraction of the social networks change the student behavior which certainly affects the viewpoint of the student to the e-learning system because of the rising of the social networks, the current study aimed, [i] to identify the use of the social networking sites in e-learning, [ii] to investigate SNS features and technologies which can be used for sharing educational materials and enhance collaboration to LMS, [iii] develop a prototype presents the integration of LMS with SNS to use its techniques for enhancing the interaction and collaboration. In order to achieve the objectives, literature review shows the uses of social networks in the e-learning field, and how to use its tools for investigating the collaboration in the e-learning system as pros with avoiding the cons of the social networking sites as e-learning systems and in the educational process. Achieving the objectives of the research need a mix method to have the best understanding and increase the quality of the final results with providing more comprehensive understanding of the study. The results have been collected from the survey and interviews showed the acceptance for integrating learning management systems with social networking sites for keeping the learning management systems in the same level of the internet rapid change in techniques evolution. The prototype has been developed as intermediate application using the platform of Facebook API for integrating Moodle learning management system to achieve high level of students‟ engagement in learning management systems by adding more collaboration tools which leads to increase the interaction between the student and the system. The prototype was tested by students, and the results confirmed that integrating LMS with SNS positively affect the goals of this research and enhancing learning management systems the means for achieving the research goals.